Are Corticosteroids Beneficial for Sepsis and Septic Shock? Based on Pooling Analysis of 16 Studies - Yao, Yang-Yang; Lin, Lu-Lu; Gu, Hui-Yun; Wu, Jun-Yi; Niu, Yu-Ming; Zhang, Chao (Frontiers in Pharmacology, 2019)
Background: A host of systematic reviews and meta-analyses were carried out to estimate the role of corticosteroids in sepsis and septic shock. Discordant opinions were investigated to determine whether patients who experienced sepsis and septic shock could benefit from corticosteroids treatment. Our purpose is to perform a systematic review of overlapping meta-analyses and explore the role of corticosteroids in the treatment of sepsis and septic shock. Method: Ovid MEDLINE, EMBase, Cochrane Database of Systematic Reviews, and LILACS were searched for eligible studies. Two authors individually extracted the relevant data and evaluated the quality of the meta-analysis using A MeaSurement Tool to Assess systematic Reviews 2 (AMSTAR 2) and ROBIS. The Jadad decision algorithm was implemented to identify the meta-analyses that offered the optimal level of evidence. Result: Sixteen meta-analyses met the eligibility criteria. None of the studies that reported mortality illustrated significant improvement on mortality (14-day and 90-day) but 28-day mortality on long course of low dose corticosteroids. Wherein, only four studies stated long course of low-dose corticosteroids had advantageous effect on 28-day mortality. A meta-analysis by Fang et.al was regarded as the highest level of evidence in the Jadad decision algorithm among the meta-analyses that were investigated in this systematic review. Conclusion: The 28-day mortality reduced via using long course of low-dose corticosteroids, as well as mortality of ICU and hospital and the length of stay in ICU, was demonstrated by meta-analysis of the current optimal available evidence. Additionally, there are significant improvement on adverse events of hyperglycaemia and hypernatraemia.